Assessment of groundwater aquifer impact from artificial lagoons and the reuse of wastewater in Qatar - Aljabiry, Hayat (2022)
Qatar is a desert where precipitation is uncommon and occurs mostly in winter. Qatar depends on desalination for drinking water and groundwater and recycled water for irrigation. There is overextraction of groundwater causing seawater intrusion. Re-use of treated wastewater (TWW) is extremely limited with only 14% of TWW being used for irrigation. This has led to the country disposing of unwanted water from various sources in artificial lagoons situated across the country where it evaporates and infiltrates the groundwater raising concerns over the possibility of environmental pollution. This is a unique situation that is limited to extremely arid countries. Research on the artificial lagoons is limited, with a noticeable knowledge gap in understanding the lagoon influence on Qatari aquifers. Accordingly, the hypothesis underpinning this research is that the quality and quantity of water in lagoons is currently having an impact on the groundwater reservoirs in Qatar. To validate this hypothesis a social survey, a hydrogeochemical survey and a microbial survey have been undertaken to establish the current situation and provide policy makers with recommendations for future lagoon management.